Method for removing impurity acetic ether from vinyl acetate

Through the selective adsorption and desorption technology of six-meal melon ring Q[6] solid powder material, the problem of complex separation process and high energy consumption in vinyl acetate is solved, and the separation effect is achieved with high efficiency and low cost. Improves the stability and reusability of the material.

CN119306600APending Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311356842.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-12
Filing Date
2023-10-19
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, the separation of vinyl acetate and ethyl acetate mainly depends on distillation method, the process is complex, the investment is large, and the energy consumption is high, making it difficult to achieve efficient and low-cost separation.

Method used

The six-membered melon ring Q[6] solid powder material is used to selectively adsorb ethyl acetate, remove impurity ethyl acetate from vinyl acetate, and separate is achieved through the formation of host and guest complexes and heating desorption, and the material can be reused.

Benefits of technology

It realizes efficient removal of ethyl acetate in vinyl acetate, the separation process is simple and energy consumption is low, which reduces production costs, and improves adsorption efficiency and material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306600A_ABST
    Figure CN119306600A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing impurity ethyl acetate from vinyl acetate, which comprises the following steps of: selectively adsorbing ethyl acetate in the vinyl acetate containing the impurity ethyl acetate by adopting a Q [6] solid powder material to remove the ethyl acetate from the vinyl acetate, and air-drying the Q [6] solid powder material at room temperature to remove a mixture adsorbed on the surface of the Q [6] solid powder material. And finally, desorbing to obtain the reusable Q [6] solid powder material. The separation process is simple to operate and low in equipment requirement; rectification operation is not needed in the separation process, energy consumption is low, energy is saved, and the production cost of vinyl acetate is reduced; the Q [6] solid powder material is high in stability and can be recycled, and the separation effect cannot be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical engineering technology, and in particular to a method for removing ethyl acetate as an impurity from vinyl acetate, and in particular to a method for removing ethyl acetate as an impurity from vinyl acetate by using Q[6] solid powder material to selectively remove ethyl acetate as an impurity. Background Art

[0002] Vinyl acetate (VAc) is a colorless, transparent liquid with a strong odor. It is one of the 50 largest chemical raw materials in the world. As an important organic chemical raw material, it is mainly used to produce derivatives such as polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), vinyl chloride-vinyl acetate copolymer (EVC), and polyacrylonitrile comonomer. These derivatives are widely used in chemical products such as coatings, slurries, adhesives, vinylon, films, vinyl copolymer resins, and acetal resins. Therefore, the purity of vinyl acetate directly affects the quality of these derivatives. Vinyl acetate produced from the existing synthesis process contains unreacted raw materials and by-products, so vinyl acetate needs to be further purified.

[0003] Ethyl acetate, also known as ethyl acetate, is an organic compound with the chemical formula C4H8O2. It is an ester with the functional group -COOR (a double bond between carbon and oxygen), and can undergo alcoholysis, aminolysis, transesterification, reduction and other common reactions of general esters. Ethyl acetate is a fast-drying solvent with excellent dissolving power. It is an excellent industrial solvent and can also be used as an eluent for column chromatography. It can be used for nitrocellulose, ethyl cellulose, chlorinated rubber and vinyl resin, cellulose acetate, cellulose acetate butyl and synthetic rubber, and can also be used for liquid nitrocellulose ink for copiers. It can be used as a solvent for adhesives and a diluent for spray paint. Ethyl acetate is an efficient solvent for many types of resins and is widely used in the production of inks and artificial leather. It is used as an analytical reagent, a standard substance for chromatographic analysis and a solvent.

[0004] At present, the main method for separating vinyl acetate and ethyl acetate is distillation, which has a complex separation process, large investment and high energy consumption. Summary of the invention

[0005] In view of the shortcomings in the art, the present invention provides a method for removing the impurity ethyl acetate from vinyl acetate, using a six-membered cucurbitacin Q[6] solid powder material to adsorb ethyl acetate in vinyl acetate, with low energy consumption and simple process.

[0006] The present invention provides a use of Q[6] solid powder material for selectively removing impurity ethyl acetate, wherein the structural formula of Q[6] solid powder material is

[0007] Preferably, the outer diameter of the Q[6] solid powder material is The cavity diameter is Port diameter is

[0008] The present invention also provides a method for removing the impurity ethyl acetate from vinyl acetate by using the Q[6] solid powder material to selectively remove the impurity ethyl acetate, characterized in that the molar ratio of the Q[6] solid powder material to the impurity ethyl acetate in the vinyl acetate is (1.5-2):1.

[0009] Preferably, the Q[6] solid powder can be desorbed, regenerated and reused after selectively adsorbing the impurity ethyl acetate.

[0010] Preferably, the Q[6] solid powder can be desorbed and regenerated for reuse after selectively adsorbing the impurity ethyl acetate, wherein the desorption and regeneration temperature is 80-100°C.

[0011] Preferably, the temperature for removing the impurity ethyl acetate from vinyl acetate is ≤20°C.

[0012] Preferably, the temperature for removing the impurity ethyl acetate from vinyl acetate is 10-20°C.

[0013] Preferably, a method for removing the impurity ethyl acetate from vinyl acetate using the Q[6] solid powder material for selectively removing the impurity ethyl acetate is provided, wherein the vinyl acetate is a mixture of vinyl acetate containing the impurity ethyl acetate.

[0014] Preferably, the mixture of vinyl acetate containing ethyl acetate as an impurity may be a crude product of vinyl acetate containing impurities obtained in large-scale industrial production.

[0015] The present invention also provides a use of Q[6] solid powder material to selectively remove impurity ethyl acetate, a method for removing impurity ethyl acetate from vinyl acetate, and an application of the Q[6] solid powder material in removing impurity ethyl acetate in the industrial production of vinyl acetate.

[0016] Compared with the prior art, the present invention has the following main advantages: the separation process is simple to operate and has low equipment requirements; the separation process does not require distillation operation, has low energy consumption, saves energy, and reduces the production cost of vinyl acetate; the present invention uses Q[6] solid powder material, which further reduces the cost compared with the crystal material used in the prior art; at the same time, the powder can adsorb ethyl acetate through multiple channels such as the cavity, port and outer wall of its molecules, and has a better adsorption efficiency than the crystal; the Q[6] solid powder material used is highly stable and can be recycled without reducing the separation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a GC characterization result diagram of vinyl acetate without impurities in Example 1;

[0018] Figure 2 This is a GC characterization result diagram of the adsorption of ethyl acetate from vinyl acetate containing ethyl acetate impurities by the Q[6] solid powder material of Example 2;

[0019] Figure 3 The Q[6] solid powder material of Example 3 after desorption 1 H NMR characterization results. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0021] Q[6] Solid powder material

[0022] Cucurbituril (also known as cucurbituril, Q[n]s or CB[n]s for short) is a highly symmetrical cage compound composed of 2n methylene bridged n glycoside urea units. The overall appearance is similar to pumpkin, and the main monomer glycoside urea is similar to gourd. Pumpkin and gourd belong to the same family of Cucurbitaceae (Latin: cucurbia), and urea is used as a raw material in the synthesis process, so it was finally named cucurbituril. The study of Q[n]s can be traced back to 1905, when German chemist Behrend and others used glycoside urea and polyformaldehyde as raw materials to synthesize a white solid that is neither soluble in water nor in organic solvents in an inorganic acid medium. At the same time, they found that the substance can form crystals with Congo red, KMnO4, AgNO3 and other substances. Due to the limitations of the test characterization technology at the time, its composition and structure were not clear, so it did not attract people's attention. With the gradual rise of supramolecular chemistry and the improvement of detection methods, Freeman, Mock and others re-examined the synthesis of the white solid and obtained complex crystals after coordinating it with calcium ions in a sulfuric acid solution. In 1981, they determined the exact structure of the six-membered cucurbitacin (Q[6]), the first member of the cucurbitacin family, by X-ray single crystal diffraction technology.

[0023] The structural data and schematic diagram of the Q[6] solid powder material of the present invention are as follows:

[0024]

[0025] parameter Serial number Q[6] outer diameter a 14.4 Cavity diameter b 5.8 Port diameter c 3.9 high d 9.1 Cavity volume 164

[0026] In addition, Q[6] solid powder material has some homologues, such as Q[5], Q[7], and Q[8]. Their structures and structural parameters are as follows:

[0027] parameter Serial number Q[5] Q[7] Q[8] outer diameter a 13.1 16.0 17.5 Cavity diameter b 4.4 7.3 8.8 Port diameter c 2.4 5.4 6.9 high d 9.1 9.1 9.1 Cavity volume 82 279 479

[0028]

[0029] A method for removing ethyl acetate as an impurity from vinyl acetate, wherein Q[6] solid powder material is used to selectively adsorb ethyl acetate in a mixture of vinyl acetate and ethyl acetate, thereby achieving the removal of ethyl acetate;

[0030] Due to the difference in molecular structure between ethyl acetate and vinyl acetate, the Q[6] solid powder material in the separation method can form a host-guest complex with ethyl acetate. The host-guest complex is unstable and will gradually decomplex when heated to above 60°C, releasing the adsorbed ethyl acetate. After the desorption process is completed, the Q[6] solid powder material can be reused without a decrease in selectivity.

[0031] The Q[6] solid powder material can be obtained by filtering and removing acid after reacting glycoside urea with polyformaldehyde, and can be directly used to remove the impurity ethyl acetate from vinyl acetate after drying.

[0032] The drying time is generally not less than 2 hours.

[0033] The adsorption time of the adsorption method changes with the changes of factors such as the sample amount, the adsorption temperature and the ratio of ethyl acetate to vinyl acetate.

[0034] Preferably, the adsorption method uses Q[6] solid powder material to selectively adsorb ethyl acetate in vinyl acetate containing ethyl acetate, and after removing ethyl acetate from vinyl acetate, the Q[6] solid powder material is air-dried at room temperature to remove the mixture adsorbed on the surface, and finally desorbed to obtain a reusable Q[6] solid powder material.

[0035] The time for air-drying Q[6] solid powder material at room temperature to remove the mixture adsorbed on the surface can be adjusted according to the sample amount. Under the condition of less than 20°C, the host-guest complex still exists stably, while the mixture of ethyl acetate and vinyl acetate adsorbed on the surface can be gradually removed. By removing the mixture adsorbed on the surface, the purity of ethyl acetate separated by adsorption is improved.

[0036] The ethyl acetate molecules adsorbed in the Q[6] solid powder material can be desorbed by heating, preferably at a temperature of 80-100° C., and the desorption time can be adjusted according to the sample amount. At this temperature, the host-guest complex is unstable, and the adsorbed ethyl acetate molecules will gradually be released, while the Q[6] solid powder material is stable. After desorption, the Q[6] solid powder material can continue to be used to remove the impurity ethyl acetate from vinyl acetate for the next cycle.

[0037] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The test methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Unless otherwise specified, all percentages and parts are by weight.

[0038] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following embodiments include:

[0039]

[0040]

[0041] When the molar ratio of Q[6] solid powder material to ethyl acetate as an impurity in vinyl acetate is (1.5-2):1, the adsorption method of the present invention is applicable.

[0042] Test Example 1: GC Detection

[0043] Related information of experimental equipment for GC detection: GC-2014 Shimadzu gas chromatograph, origin: Japan.

[0044] Detection experimental steps:

[0045] 1. Check the plug and connection lines to see if they are connected properly; check the air pipe connection and whether the liquid level of the hydrogen generator is within the allowable working range.

[0046] 2. Open the valve of the carrier gas (N2) cylinder, the fuel gas (H2) generator, and the power supply of the auxiliary fuel gas (compressed air) generator.

[0047] 3. Rotate the pressure reducing adjusting screw to make the secondary pressure gauge indicate the required pressure. The carrier gas is about 0.7Mpa, and the fuel gas and auxiliary gas are 0.3Mpa.

[0048] 4. Turn on the main power switch of the host. The touch screen display of the host is in self-checking and the blower motor in the column chamber is running.

[0049] 5. Turn on the computer connected to the gas chromatograph and run the gas chromatograph working software.

[0050] 6. After the software is successfully connected to the instrument, set the split ratio to 50, SPL1 temperature to 250℃, SFID1 temperature to 280℃, column oven temperature to 50℃, and running time to 25min on the control panel.

[0051] 7. After setting the parameters according to the specified analysis method, run the system and the temperature of each zone will begin to rise toward the set value. When the temperature reaches the set value, the READY light will turn on and the ignition will start.

[0052] 8. Check whether the instrument baseline is stable. Once the baseline is straight, you can run a single injection test and use a 10u injection needle to inject 1ul of sample from the injection port.

[0053] 9. After the test, click "Shut down system" on the work button, and then restore the detector, injection port, and column temperature settings to room temperature. When the temperature of the chromatographic column and injection port drops below 100°C, turn off the chromatograph power switch and computer power in turn, and finally turn off the hydrogen generator, air generator power, and nitrogen cylinder main valve.

[0054] Test sample: high purity, impurity-free vinyl acetate

[0055] Peak table

[0056] SFID1

[0057] Peak Retention time area high concentration Concentration Unit mark Compound Name 1 2.471 119915126 28341825 100.000 S total 119915126 28341825

[0058] From the above table and Figure 1 It can be seen that the retention time of peak 1 is the time when vinyl acetate elutes in the gas chromatograph. The peak height represents the signal value output by the detector when vinyl acetate elutes from the column at the maximum concentration. The size of the peak area represents the amount of the substance, which here represents the content of vinyl acetate.

[0059] Example 1: Adsorption of ethyl acetate in vinyl acetate by Q[6] solid powder material

[0060] At room temperature and pressure, take a 20mL bacterial culture bottle, add 5mL of vinyl acetate containing ethyl acetate (prepared according to the ratio of 99.961wt% vinyl acetate content and 0.039wt% ethyl acetate content), take 30mg Q[6] solid powder material and place it in the bacterial culture bottle, seal it, and place it at 20℃ for 48 hours to air-dry the obtained powder. (If the placement time is shortened, the ethyl acetate in the vinyl acetate may not be completely adsorbed)

[0061] After the adsorption is completed, the remaining vinyl acetate in the culture bottle can be measured by gas chromatography to detect whether there is any ethyl acetate residue in the vinyl acetate.

[0062] Test Example 2: GC Detection

[0063] Related information of experimental equipment for GC detection: GC-2014 Shimadzu gas chromatograph, origin: Japan.

[0064] Detection experimental steps:

[0065] 1. Check the plug and connection lines to see if they are connected properly; check the air pipe connection and whether the liquid level of the hydrogen generator is within the allowable working range.

[0066] 2. Open the valve of the carrier gas (N2) cylinder, the fuel gas (H2) generator, and the power supply of the auxiliary fuel gas (compressed air) generator.

[0067] 3. Rotate the pressure reducing adjusting screw to make the secondary pressure gauge indicate the required pressure. The carrier gas is about 0.7Mpa, and the fuel gas and auxiliary gas are 0.3Mpa.

[0068] 4. Turn on the main power switch of the host. The touch screen display of the host is in self-checking and the blower motor in the column chamber is running.

[0069] 5. Turn on the computer connected to the gas chromatograph and run the gas chromatograph working software.

[0070] 6. After the software is successfully connected to the instrument, set the split ratio to 50, SPL1 temperature to 250℃, SFID1 temperature to 280℃, column oven temperature to 50℃, and running time to 25min on the control panel.

[0071] 7. After setting the parameters according to the specified analysis method, run the system and the temperature of each zone will begin to rise toward the set value. When the temperature reaches the set value, the READY light will turn on and the ignition will start.

[0072] 8. Check whether the instrument baseline is stable. Once the baseline is straight, you can run a single injection test and use a 10u injection needle to inject 1ul of sample from the injection port.

[0073] 9. After the test, click "Shut down system" on the work button, and then restore the detector, injection port, and column temperature settings to room temperature. When the temperature of the chromatographic column and injection port drops below 100°C, turn off the chromatograph power switch and computer power in turn, and finally turn off the hydrogen generator, air generator power, and nitrogen cylinder main valve.

[0074] Test sample: Powder obtained in Example 1

[0075] Peak table

[0076] SFID1

[0077] Peak Retention time area high concentration Concentration Unit mark Compound Name 1 2.418 63087 23025 8.321 2 2.545 695054 224524 91.679 total 758141 247549

[0078] From the above table and Figure 2 It can be seen that the retention position 2.418 of peak 1 is the elution position of vinyl acetate, and the retention position 2.545 of peak 2 is the elution position of ethyl acetate. As can be seen from the figure, the adsorption rate of Q[6] for ethyl acetate is 91.679%, and the adsorption rate for vinyl acetate is 8.321%. It can be seen that Q[6] can well separate ethyl acetate from vinyl acetate.

[0079] Example 2: Regeneration of Q[6] solid powder material

[0080] 30 mg of the Q[6] solid powder material subjected to supersaturated adsorption of ethyl acetate in Example 1 was heated in a vacuum oven at 100° C. for 2 hours. The sample was designated as Q[6]-D and kept for later use.

[0081] Test Example 3: 1 H NMR detection

[0082] Instrument related information: JNM ESC400M nuclear magnetic resonance spectrometer, single-phase 220v 50Hz 3Kw, manufacturer Japan.

[0083] Experimental steps and main parameters:

[0084] 1. Double-click the DELTA icon on the computer desktop to enter the NMR spectrometer operating software system, connect the spectrometer and the magnet, and enter the user name Delta and password Delta to log in to the spectrometer control interface.

[0085] 2. Add a sample menu item in the Sample tab, create a sample name, select D2O as the deuterated reagent and put it into the corresponding sample slot code. After confirming that it is correct, create the determination (Job title) corresponding to the sample in the lower right corner of the Sample tab.

[0086] 3. Select Hydrogen Spectrum under Job title, set the number of scans to 32 times in the experimental parameter interface, and after confirmation, click Submit Job in the lower right corner.

[0087] 4. After the experiment is completed, the operator should lock the sample and stop rotating the NMR tube, click the button (Eject), take the NMR tube out of the magnet and place it on the automatic sampler, and finally process the data results of the sample.

[0088] Test sample: Regenerated powder Q[6]-D obtained in Example 2

[0089] Q[6]-D, 1H NMR(400MHz,D2O,298K,ppm)δ16.00(d,12H),5.53(s,12H),16.00(d,12H)

[0090] Depend on Figure 3 It is known that in 1 In the H NMR spectrum, it was found that the signal of the hydrogen atom corresponding to ethyl acetate had disappeared, which indicated that the Q[6] solid powder material had completed desorption and regeneration, and all the ethyl acetate molecules had been released.

[0091] Examples 3, 5, 7, 9: Adsorption of ethyl acetate in vinyl acetate by Q[6] solid powder material

[0092] The steps of Examples 3, 5, 7, and 9 are basically the same as those of Example 1, except for the amount of Q[6] used and the temperature at which the impurity ethyl acetate is selectively removed from the vinyl acetate, as shown in the following table:

[0093]

[0094] Examples 4, 6, 8, 10: Regeneration of Q[6] solid powder material

[0095] Examples 4, 6, 8, and 10 correspond to Examples 3, 5, 7, and 9, respectively, and are substantially the same as the steps of Example 2, except for the temperature of the vacuum oven, as shown in the following table:

[0096] Serial number Vacuum oven temperature Example 2 100℃ Example 4 80℃ Example 6 85℃ Example 8 90℃ Example 10 95℃

[0097] After testing, the experimental effects of Examples 3, 5, 7, and 9 are equivalent to those of Example 1, and the experimental effects of Examples 4, 6, 8, and 10 are equivalent to those of Example 2.

[0098] In summary, the method for selectively removing the impurity ethyl acetate by using the Q[6] solid powder material provided by the present invention has a simple separation process and low equipment requirements; the separation process does not require distillation operation, has low energy consumption, saves energy, and reduces the production cost of ethyl acetate and vinyl acetate; the present invention uses Q[6] solid powder material, which further reduces the cost compared with the crystal material used in the prior art; at the same time, the powder can adsorb ethyl acetate through multiple channels such as the cavity, port and outer wall of its molecules, and has a better adsorption efficiency than the crystal; the Q[6] solid powder material used is highly stable and can be recycled without reducing the separation effect.

[0099] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. Use of Q[6] solid powder material for selectively removing impurity ethyl acetate, wherein the structural formula of Q[6] solid powder material is 2. The use according to claim 1, characterized in that The outer diameter of the Q[6] solid powder material is The cavity diameter is Port diameter is 3. A method for removing impurity ethyl acetate from vinyl acetate using the use as claimed in claim 1, characterized in that: The molar ratio of the Q[6] solid powder material to the ethyl acetate in the vinyl acetate is (1.5-2):

1.

4. The method according to claim 3, characterized in that The vinyl acetate is a mixture of vinyl acetate containing ethyl acetate as an impurity.

5. The method according to claim 4, characterized in that The mixture of vinyl acetate containing ethyl acetate as an impurity is a crude product of vinyl acetate containing impurities obtained from large-scale industrial production.

6. The method according to claim 3, characterized in that The temperature for removing the impurity ethyl acetate from vinyl acetate is ≤20°C.

7. The method according to claim 6, characterized in that The temperature for removing the impurity ethyl acetate from vinyl acetate is 10-20°C.

8. The method according to claim 3, characterized in that After selectively adsorbing the impurity ethyl acetate, the Q[6] solid powder can be desorbed, regenerated and reused.

9. The method according to claim 8, characterized in that The desorption regeneration temperature is 80-100℃。 10. Use of the method according to any one of claims 3 to 9 in removing impurity ethyl acetate in the industrial production of vinyl acetate.